2011
DOI: 10.1017/s0024282911000508
|View full text |Cite
|
Sign up to set email alerts
|

The cetrarioid core group revisited (Lecanorales: Parmeliaceae)

Abstract: The cetrarioid core group has been the focus of numerous taxonomic and phylogenetic studies in recent years, yet the phylogenetic resolution and support among these clades remains unclear. Here we use four commonly employed loci to estimate if their use increases phylogenetic resolution and support. The present study largely confirms the topologies of previous studies, but with increased support. Approximately half of the genera in the cetrarioid core were not monophyletic. Melanelia sorediella was clustered w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 52 publications
2
63
0
Order By: Relevance
“…The cetrarioid core group was reconstructed as monophyletic (but not strongly supported, if Melanelia is included) and in general agreement with Thell et al (2009) and Nelsen et al (2011). Our study confirms the monophyly of the hypogymnioid group as previously circumscribed (Crespo et al, 2007), possibly with the genus Evernia resulting from the first phylogenetic split in this clade.…”
Section: Resultssupporting
confidence: 61%
“…The cetrarioid core group was reconstructed as monophyletic (but not strongly supported, if Melanelia is included) and in general agreement with Thell et al (2009) and Nelsen et al (2011). Our study confirms the monophyly of the hypogymnioid group as previously circumscribed (Crespo et al, 2007), possibly with the genus Evernia resulting from the first phylogenetic split in this clade.…”
Section: Resultssupporting
confidence: 61%
“…Ach. In the most recent molecular studies of cetrarioid lichens (Thell et al 2009;Nelsen et al 2011) based on more markers, C. aculeata and C. muricata were always treated as separate species. At least two additional close relatives of C. aculeata have so far been described, the corticolous C. crespoae (Barreno & Vázquez) Kärnefelt from western Spain and C. steppae (Savicz) Kärnefelt from Ukraine containing norstictic acid (Kärnefelt et al 1993).…”
Section: Delimiting Species Within the Cetraria Aculeata Groupmentioning
confidence: 99%
“…1B) had previously been considered a form of Cetraria crispa (Ach.) Subsequently, Thell et al (2009) demonstrated a distant relationship between these two taxa based on molecular sequence data, and both Thell et al (2009) andNelsen et al (2011a) have instead suggested a close relationship between M. inermis (as T. inermis) and M. richardsonii. Krog (1973) elevated it to the species level as Cetraria inermis (Nyl.)…”
Section: Introductionmentioning
confidence: 99%